Copper(I)‐Catalyzed Wittig Olefination Reactions of N‐Tosylhydrazones with Trifluoromethylketones. Issue 1 (23rd October 2013) - Sha, Qiang; Wei, Yunyang
Abstract Cuprous iodide‐catalyzed Wittig olefination reactions of N‐tosylhydrazones with trifluoromethylketones are reported. This procedure provides an efficient method for the synthesis of various trifluoromethyl‐substituted alkenes in moderate to good yields (up to 89 % yield) and good stereoselectivity (up to 93 % E‐selectivity). To the best of our knowledge, it is the first report of a Wittig reaction of N‐tosylhydrazones with ketones.